EVALUASI PERLINDUNGAN GARDU INDUK 150 KV PANDEAN LAMPER DI TRAFO III 60 MVA TERHADAP GANGGUAN SURJA PETIR - Ihwan Ernanto Wibowo; Luqman Assaffat; M. Toni Prasetyo (PSTE UNIMUS, 2012)
One of the main causes of damage to existing equipment in the substation was struck bylightning attack that cause the conductor wave and make over voltage and flames leap peak voltage exceeds BIL. The aim of this study was to calculate and analyze the level of protection, against power transformer arrester, the safe distance between arrester and transformer power to get a good protection against harmful lightning surges, comparing both arresters installed. To solve the problems of interference caused by lightning surge lightning arrester is installed as close as possible to put on the transformer clamps to protect electrical equipment. The results of calculations for a distance of 6 m, 4 MBA type 2 arrester capable of with standing the wavefront steepness of 500 kV / μs, while type exlim P 700 kV / μs. The greater the arrester capable of withstanding surge wavefront tilting the better the equipment in substations are protected. The evaluation shows that the distance between arrester and transformer installed in the 150 kV substation Pandean Lamper less than the maximum to protect electrical equipment, especially power transformers.Key words : lightning attack, arrester distance, level of protection.